Arctic National Wildlife Refuge : visitor information. - U.S. Fish and Wildlife Service. ([Washington, D.C.? : U.S. Dept. of the Interior, Fish and Wildlife Service, 1982)
Shipping list no.: 86-658-P. Mode of access: Internet.